QR Code Information at Metro Stations: Creating Convenience and Access to Information for Passengers (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article explores the possibilities of creating convenience and obtaining information for passengers by introducing QR code technology in the subway. Through the use of QR codes, passengers are provided with quick information about the history of subway stations, timetables, exits and additional services. Using modern technologies, this project will save passengers' time, increase the convenience of using the transport system, and develop urban tourism. Technical possibilities and limitations are also considered.